1973
DOI: 10.1126/science.182.4117.1136
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evidence for a Colchicine-Induced Impairment in the Mobility of Membrane Components

Abstract: Freeze-etch electron microscopy was used to show that colchicine interacts with membranes of the ciliate protozoan Tetrahymena pyriformis. Colchicine impairs the temperature-induced translational and vertical mobility of the membrane-intercalating particles of the freeze-fractured alveolar membranes lying just below the plasma membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1975
1975
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Consideration should also be given to a possible direct effect of colchicine on membranes and their topography . Colchicine impaired the movement of membrane particles in the alveolar membrane of Tetrahymena pyriformis (49) and bound to rat liver Golgi membranes and increased their fluidity (23) . Such effects might explain the influence of colchicine in inhibiting the selective uptake of concanavalin A binding sites during phagocytosis by polymorphonuclear leukocytes (27), concanavalin A-induced agglutination of hepatoma cells (24), and the appearance of augmented amino acid transport capacity after partial hepatectomy (46), although an influence via microtubular effects cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Consideration should also be given to a possible direct effect of colchicine on membranes and their topography . Colchicine impaired the movement of membrane particles in the alveolar membrane of Tetrahymena pyriformis (49) and bound to rat liver Golgi membranes and increased their fluidity (23) . Such effects might explain the influence of colchicine in inhibiting the selective uptake of concanavalin A binding sites during phagocytosis by polymorphonuclear leukocytes (27), concanavalin A-induced agglutination of hepatoma cells (24), and the appearance of augmented amino acid transport capacity after partial hepatectomy (46), although an influence via microtubular effects cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…During dedifferentiation and loss of specific cell functions such as protein secretion (32), the elaborate transport systems may also dedifferentiate, and uptake of nutrients would possibly be achieved by simple processes such as micropinocytosis, for example. These new uptake mechanisms could depend on variables such as plasma membrane microviscosity or the lateral mobility of membrane components, both of which are affected by colchicine (10,11). The effect of colchicine and vinblastine could be due to changes in composition (33) and turnover (15,34) of membrane proteins and glycoproteins in hepatomas.…”
Section: Methodsmentioning
confidence: 99%
“…Microtubule-associated functions may also regulate lysosomal degranulation during phagocytosis (7,8) and influence the conversion of prohormones into their active forms (9). The colchicine-induced inhibition of the mobility of membrane components (10) and changes in plasma membrane microviscosity associated with phagocytosis (11) may reflect the close relationship between the microtubular system and the cell membrane.…”
mentioning
confidence: 99%
“…Examination of the reports of some authors will lead us to a mechanism which concerns both binding to membranes and microtubules. Wunderlich et al (1973), Furcht and Scott (1975) and Furcht et al (1976) showed that colchicine alters mobility or topography of membrane components on normal or transformed cells. On the other hand, Tamura (1971) showed blockade of transference of newly synthesized microtubule protein to particulate fraction within colchicine treated cells.…”
mentioning
confidence: 99%